Building An Investment Paradigm for A Better Future Through Capital Market Education - Maria Immaculata Yovita Adventy; M. Yogi Dwi Nalapraya; Aru Bina Bangsawan; Selma Kemuning Aquinta; Adellah Adellah (Social Science Academic, 2026)
The low level of financial literacy among Indonesians remains a significant challenge in achieving sustainable economic well-being. Most people still rely primarily on active income and consider savings as the main financial management instrument without taking into account the impact of inflation on the value of money. This community service activity aimed to enhance participants’ understanding of the importance of investment and introduce the capital market as a legal, safe, and affordable investment alternative. The methods employed included interactive lectures, case studies, group discussions, and basic investment simulations. The results indicated an improvement in participants’ understanding of the Cash Flow Quadrant concept, the importance of investment in long-term financial planning, and the mechanisms of investing in the capital market. Participants also gained knowledge regarding investment risk mitigation and strategies to avoid fraudulent investment schemes. Overall, the activity successfully shifted participants’ perspectives from an active-income-oriented mindset toward a greater awareness of the importance of building assets and generating passive income through investment.